2021
DOI: 10.1111/ppl.13611
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide discovery ofDNApolymorphisms via resequencing of chickpea cultivars with contrasting response to drought stress

Abstract: Drought stress limits plant growth, resulting in a significant yield loss in chickpea. The diversification in genome sequence and selective sweep of allele(s) in different genotypes of a crop plant may play an important role in the determination of agronomic traits, including drought stress response. We investigated, via whole genome res-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 84 publications
(168 reference statements)
0
9
0
Order By: Relevance
“…We identified all the transcripts located within the drought tolerance associated known QTL regions 49 52 and analyzed their expression profiles using RNA-seq data of a drought-tolerant (Dtol; ICC 4958) and a drought-sensitive (Dsen; ICC 1882) chickpea genotype under control (CT) and drought stress (DS) conditions at early reproductive (ER) and late reproductive (LR) stages from our previous study 53 . Further, the differentially expressed transcripts were examined for the presence of DNA polymorphisms that differentiate drought-sensitive and drought-tolerant chickpea genotypes 54 . The analysis revealed a total of 65 differentially expressed transcripts that harbored the DNA polymorphisms within the transcripts and/or their promoter regions (Supplementary Data 10 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We identified all the transcripts located within the drought tolerance associated known QTL regions 49 52 and analyzed their expression profiles using RNA-seq data of a drought-tolerant (Dtol; ICC 4958) and a drought-sensitive (Dsen; ICC 1882) chickpea genotype under control (CT) and drought stress (DS) conditions at early reproductive (ER) and late reproductive (LR) stages from our previous study 53 . Further, the differentially expressed transcripts were examined for the presence of DNA polymorphisms that differentiate drought-sensitive and drought-tolerant chickpea genotypes 54 . The analysis revealed a total of 65 differentially expressed transcripts that harbored the DNA polymorphisms within the transcripts and/or their promoter regions (Supplementary Data 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…8b and Supplementary Table 6 ). Several TFs cognate to these cis -regulatory motifs have been implicated in drought stress responses/tolerance 54 57 . These transcripts and/or alleles represent important candidates for prioritization to validate their role in drought tolerance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 2488 SNPs had a high impact due to the gain of stop codons, variations in splice acceptors and splice donors, and the loss of start codons. Similarly, analysis of WGRS data obtained from nine chickpea genotypes (3 of which were drought‐sensitive and 6 were drought‐tolerant) led to the identification of 36,406 SNPs and 3407 insertions or deletions that distinguish the drought‐sensitive and drought‐tolerant genotypes (Rajkumar et al, 2022). Moreover, Tang et al (2022) identified 66 U‐box genes encoding ubiquitin ligases in the potato genome.…”
mentioning
confidence: 99%